2016
DOI: 10.1371/journal.pone.0161526
|View full text |Cite
|
Sign up to set email alerts
|

Distinct 3D Architecture and Dynamics of the Human HtrA2(Omi) Protease and Its Mutated Variants

Abstract: HtrA2(Omi) protease controls protein quality in mitochondria and plays a major role in apoptosis. Its HtrA2S306A mutant (with the catalytic serine routinely disabled for an X-ray study to avoid self-degradation) is a homotrimer whose subunits contain the serine protease domain (PD) and the regulatory PDZ domain. In the inactive state, a tight interdomain interface limits penetration of both PDZ-activating ligands and PD substrates into their respective target sites. We successfully crystalized HtrA2V226K/S306A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 63 publications
1
23
0
Order By: Relevance
“…The simulations demonstrated that upon binding of a specific peptide ligand (GWTMFWV) the PDZ domains rotate vs. PD by~30 -50 , opening the PD-PDZ interface in a lid-like (budding flower-like in trimer) fashion. Furthermore, the opening of the subunit interfaces progresses in a sequential manner [132]. These changes are consistent with the thermal induction model [123] though it is not possible to state if the extent of the PDZ rotation stimulated by the peptide binding is similar to the one caused by the temperature increase.…”
Section: Allosteric Activation Of Htra2supporting
confidence: 56%
See 2 more Smart Citations
“…The simulations demonstrated that upon binding of a specific peptide ligand (GWTMFWV) the PDZ domains rotate vs. PD by~30 -50 , opening the PD-PDZ interface in a lid-like (budding flower-like in trimer) fashion. Furthermore, the opening of the subunit interfaces progresses in a sequential manner [132]. These changes are consistent with the thermal induction model [123] though it is not possible to state if the extent of the PDZ rotation stimulated by the peptide binding is similar to the one caused by the temperature increase.…”
Section: Allosteric Activation Of Htra2supporting
confidence: 56%
“…These changes are consistent with the thermal induction model [123] though it is not possible to state if the extent of the PDZ rotation stimulated by the peptide binding is similar to the one caused by the temperature increase. The MDS studies pointed also to the fact that the position of the L3 loop in the generated active HtrA2 is different from a canonical position present in any active HtrA protein, enabling L3 to make contact with the LD* loop [132]. This seems to be an important issue which needs clarification.…”
Section: Allosteric Activation Of Htra2mentioning
confidence: 98%
See 1 more Smart Citation
“…Most studied amyloid beta (Aβ) peptides includes Aβ (1-16), Aβ (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), Aβ (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), Aβ (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33), Aβ , Aβ (23-34), Aβ (34)(35)(36)(37)…”
Section: Racemization Of the Aβmentioning
confidence: 99%
“…Coincidence of phosphorylation and racemization at Ser and Asp residues of Aβ (1-42). Beta (1-42) N- Terminal 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 C-Terminal Asp Ala Glu Phe Arg His Asp Ser Gly Tyr Glu Val His His Gln Lys Leu Val Phe Phe Ala Glu Asp Val Gly Ser Asn Lys Gly Ala Ile Ile Gly Leu Met Val Gly Gly Val Val Ile Ala First, the pathological role of mitochondrial enzymes Ser proteases (SerPs) is attributed to neurodegenerative disorders such as AD and Parkinson's and disease [25][26][27]. The HtrA (high-temperature requirement) family represents a class of oligomeric SerPs [25].…”
Section: The Frequency (F) Of the Aas Appearance Inmentioning
confidence: 99%